ORIENTASI KEWIRAUSAHAAN DAN KINERJA IKM SEKTOR PARIWISATA: A SYSTEMATIC LITERATURE REVIEW - Ryna Parlyna; Perengki Susanto; Abror Abror (Jurnal Ilmu Manajemen, 2022)
This study aims to systematically identify, review, and assess the entrepreneurial orientation literature with small-medium enterprise performance and provide an agenda for future research. The current study assesses the existing scholarship on the topic, reveals the limitations and gaps in the current body of literature, and suggests potential studies for further advancement of knowledge in this area. This study employs a Systematic Literature Review using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis) method. A systematic literature review aims to bring as much existing evidence-based research as possible relevant to the research being done. This research uses the keywords entrepreneurial orientation", "entrepreneurship", and "Small Medium Enterprise performance, SME's performance, the relationship between entrepreneurial orientation on SME's performance, the impact of entrepreneurial orientation on SME performance, entrepreneurial orientation on SME's performance, entrepreneurial orientation, SME's Tourism performance" to get the article. The sample of 38 studies was selected from such databases as Science Direct, Sage, and Emerald. The content analysis, assisted by Microsoft Excel, was employed for review and analysis purposes.